Prevalence of asymptomatic Bordetella pertussis and Bordetella parapertussis infections among school children in China as determined by pooled real-time PCR: A cross-sectional study. (April 2014) - Zhang, Qi; Yin, Zundong; Li, Yixing; Luo, Huiming; Shao, Zhujun; Gao, Yuan; Xu, Li; Kan, Biao; Lu, Shan; Zhang, Yan; Li, Manshi; Liu, Meizhen; et al.
Abstract Background: Studies have documented that older children and adolescents act as a reservoir of Bordetella pertussis infection for young infants who have not yet completed their primary immunization schedule. Asymptomatic pertussis infection has been reported during outbreaks. This cross-sectional study aimed to investigate whether B. pertussis and Bordetella parapertussis can colonize the nasopharynx of healthy school children, using culture and pooled real-time PCR with targets for insertion sequences IS481 and IS1001. Methods: Nasopharyngeal (NP) swabs were taken from 629 asymptomatic school children aged 7 to 15 y in 4 counties of China during the period July–September 2011. The number of subjects included in each county ranged from 153 to 165. The 4 counties selected are located in the north, south, east, and southwest regions of China. NP swabs were inoculated onto Regan–Lowe agar for isolation of suspected Bordetella organisms. Pooled real-time PCRs were used to detect B. pertussis and B. parapertussis based on the IS481 and IS1001 targets separately. Results: Of the 629 subjects, 2 (0.3%) and 30 (4.8%) were confirmed to be culture-positive and PCR-positive, respectively, for B. pertussis, and 1 (0.2%) and 13 (2.1%) were confirmed to be culture-positive and PCR-positive, respectively, for B. parapertussis. All culture-positive samples were also PCR-positive. Furthermore, positive B. pertussis and B. parapertussis samples were found in all counties. Conclusions: Our results indicate that asymptomatic B. pertussis infections are common in school children in China, and asymptomatic B. parapertussis infections are more prevalent than previously documented.